UMA ANÁLISE SOBRE A RESOLUÇÃO DE PROBLEMAS NO CURSO DE LICENCIATURA EM MATEMÁTICA DA UNIVERSIDADE FEDERAL DE MATO GROSSO DO SUL NO CAMPUS DE PONTA PORÃ (2009 – 2022) - JOSÉ AUGUSTO GUEVARA DELGADO (2024)
The objective of this research was to investigate what representation about Problem Solving appears in a Mathematics Degree course and, if there is such a representation, it can be considered knowledge for the professional training of mathematics teachers. For this investigation, we used Cultural History as a theoretical-methodological foundation, as it provided us with the notion of collective representation, which helped us understand how Problem Solving was included in the Mathematics Degree course, and how it understood Resolution Problems, we also use other concepts, such as School Culture and History of School Subjects, which are objects of study in the field of History of mathematical education. To develop this research, we verified the Pedagogical Projects of the Mathematics Degree Course at the Federal University of Mato Grosso do Sul, on the Ponta Porã campus, from 2009 to 2022, in addition to teaching plans and official documents from the government and the Federal University of Mato Grosso do Sul that internally influenced the Mathematics course. Throughout the analyses, we identified characteristics of the School Culture of the Degree in Mathematics course at the Ponta Porã Campus, noting that the course was designed considering the regional reality in which it was located, we also identified influences from external documents, which affected characteristics and disciplines of the course. We show throughout these analyzes how the collective representation of the course regarding Problem Solving has changed over the years, from 2009 to 2022, becoming the teaching methodology with the greatest presence in the curriculum.